2022
DOI: 10.1371/journal.pone.0262490
|View full text |Cite
|
Sign up to set email alerts
|

Disparities by race and insurance-status in declines in pediatric ED utilization during the COVID19 pandemic

Abstract: Pediatric Emergency Department (ED) utilization in the U.S. saw large declines during the COVID19 pandemic. What is relatively unexplored is whether the extent of declines differed by race and insurance status. An observational study was conducted using electronic medical record (EMR) data from the largest pediatric ED in Alabama for 2020 and 2019. The four subgroups of interest were African-American (AA), Non-Hispanic White (NHW), privately insured (PRIVATE), and publicly insured or self-insured (PUBLIC-SELF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Individuals with lower socioeconomic status, public insurance and those from marginalized populations were less likely to seek care in an ED during the pandemic (Lowe et al 2021 ). This is in contrast to ED utilization prior to the pandemic where individuals with public insurance were more likely to utilize the ED for various reasons, such as less access to after-hours primary care (Sen et al 2022 ; Chande et al 1996 ). In our study, there was a decrease in the median deprivation index of those individuals who sought PED care in 2020, indicating less PED visits from socioeconomically disadvantaged areas.…”
Section: Discussionmentioning
confidence: 95%
“…Individuals with lower socioeconomic status, public insurance and those from marginalized populations were less likely to seek care in an ED during the pandemic (Lowe et al 2021 ). This is in contrast to ED utilization prior to the pandemic where individuals with public insurance were more likely to utilize the ED for various reasons, such as less access to after-hours primary care (Sen et al 2022 ; Chande et al 1996 ). In our study, there was a decrease in the median deprivation index of those individuals who sought PED care in 2020, indicating less PED visits from socioeconomically disadvantaged areas.…”
Section: Discussionmentioning
confidence: 95%
“…We would like to use a validated survey instrument and include additional variables such as modalities of telehealth visits, residence distance from the hospital, type of insurance coverage, and other covariates in the future to shed more light on telehealth barriers in the Deep South region. Second, caution must be exercised when generalizing the study findings, since this was based on a convenience sample of pediatric patients who continued to present to an ED of a children’s hospital during the COVID19 pandemic, and this choice might be influenced by the family’s socio-economic status, as well as attitudes and beliefs about the risk of COVID19 infections [ 22 ]. Third, we used income and marital status as a proxy for socioeconomic status, but could not include race-ethnicity information, thus our ability to fully investigate disparities in telehealth utilization is limited.…”
Section: Discussionmentioning
confidence: 99%
“…13 Given that minority race and Medicaid or non-insured patients are more likely to present to the ED for care as they lack other avenues, this implies an increase in healthcare disparities during the pandemic. 13 Similarly, in a study from the pediatric otolaryngology department at Children's Hospital Los Angeles during COVID, the authors found that no show appointments were more common in Hispanic patients and those who lived in a zip code that had a median income of less than 200% of the federal poverty level. 14 In keeping with these known disparities, we hypothesized that we would see a greater delay in presentation and surgery in minority patients and in those with Medicaid/no insurance during the pandemic compared to before.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of pediatric ED utilization during the pandemic compared to prior, an overall decline in ED use across all races was noted with a more significant decrease noted in African American patients compared to non-Hispanic whites and in those with Medicaid or no insurance compared to those with private insurance. 13 Given that minority race and Medicaid or non-insured patients are more likely to present to the ED for care as they lack other avenues, this implies an increase in healthcare disparities during the pandemic. 13 Similarly, in a study from the pediatric otolaryngology department at Children's Hospital Los Angeles during COVID, the authors found that no show appointments were more common in Hispanic patients and those who lived in a zip code that had a median income of less than 200% of the federal poverty level.…”
Section: Discussionmentioning
confidence: 99%